Rancang Bangun Mesin Pengiris dan Penggoreng Umbi-Umbian Berbasis Mikrokontroler Atmega 8535 - Ahmad Ansari Amini; Parlin Siagian; Solly Aryza (Journal Serambi Engineering, 2024)
Design and Construction of Microcontroller Based Tubers Slicing and Frying Machine ATmega 8535, this machine is expected to help the production of processed chips. In making this tuber chips machine, there are three processes that will be carried out including the cutting process, the drying process and the frying process. This system uses an ATmega 8535 microcontroller which functions to control this tool to work according to the program that has been made. For the cutting process is done semi-automatically with a cutting knife driven by a 1 phase induction motor. In the process of drying tubers, a dryer is used, which functions to dry the sliced tubers so that when frying the sliced tubers do not accumulate because they are wet.